E-Learning in der Lehramtsausbildung am Beispiel des Seminars „Anwendungsorientierter Mathematikunterricht“: Konzept, Entwicklungsprozess und Erfahrungsbericht (mathematica didactica, 2004)
As part of the pedagogical education of teachers in mathematics for high schools and vocational schools an elective course has been established at Darmstadt University of Technology about the concept, shape and reflections of practically oriented lessons in mathematics. During the last two years this course, which initially was offered in form of a seminar, has been developed into a computer based course. This is a report about the development and the concept of the computer based course as well as the present status and the results obtained.